PEMIKIRAN MUHAMMAD IQBAL TENTANG PENDIDIKAN KARAKTER DAN RELEVANSINYA DENGAN ERA DISRUPSI - Masluhah Masluhah; Kiki Rizkiatul Afifah; Mohamad Salik (Ta'allum: Jurnal Pendidikan Islam, 2021)
Abstract: Muhammad Iqbal is a Philosopher and education’s figure. His saveral ideas are about character education and education of creativity. Disruption era brings a complex problem, especially in moral and character development. The deterioration of student’s moral value will be a trigger to make attitude and behavior that doesn’t suit with spiritual value or the oble values of Indonesian nation. Therefore, character development in disruption era be a very important discussion. This research aims to analyze Muhammad Iqbal’s views of character education that relevance to disruption era. The research’s method is library research with data collection techniques from any references such as books, journals, newspaper, and others articles. This research used descriptive analysis technique. The results is according to Muhammad Iqbal’s thoughts that character education is an effort to prevent the moral crisis phenomenon on students that relevant at disruption era. Impementation of the character education is with modelling of positive character and behavior, development self-awareness about human essence as insan kamil, and developement the tolerance.